SINKRETISME AGAMA DAN BUDAYA: Tradisi Sumpah Menggunakan Al-Quran Khatam Rayab - Exsan Adde; Savri Yansah (Universitas Islam Negeri Imam Bonjol Padang, 2021)
This research is motivated by the problems raised in Religious and Cultural Syncretism: The Tradition of the Oath Using the Al-Quran Khatam Rayab. Khatam Rayab is an ancient Koran found in Karang Baru Village, Padang Ulak Tanding District, which is used to solve problems that cannot be resolved amicably and legally. The purpose of this study was to determine the process of implementing the oath using the Koran Khatam Rayab. This research is a field research that uses qualitative descriptive methods, taking research topics or respondents using ethnographic methods. Ethnography is an approach used to understand how people in a community interact and are observed in everyday life. Ethnography is used to examine human behavior related to the development of communication technology in certain social and cultural settings. In this study, the researchers used an approach of observation, interviews, documentation, and data analysis techniques, namely data reduction, data presentation and conclusion drawing, which became the research of the owner of Khatam Rayab Mr. Hur, Joko's heir, people who had promised and the community. Based on the research results of Religious and Cultural Syncretism: Tradition of Oaths Using the Khatam Rayab Al-Quran, namely at the stage before the implementation of the oath, offerings and dowries are in the form of cash. The da'wah values contained in the tradition are: life values, discipline values, social values, cultural values and honesty values.Â Berdasarkan hasil penelitian Sinkretisme Agama dan Budaya: Tradisi Sumpah Menggunakan Al-Quran Khatam Rayab yaitu pada tahapan proses sebelum melaksanakan sumpah harus menggunakan sesaji dan mahar berupa uang tunai. Nilai-nilai dakwah yang terdapat dalam tradisi tersebut yaitu: nilai keimanan, nilai kedisiplinan, nilai sosial, nilai budaya dan nilai kejujuran.Â